Pengembangan Sistem Manajemen dan Pemesanan Jasa Pekerja Rumah Tangga berbasis Web (Studi Kasus : CV Sitiari) - Ary Muhammad Prayoga; Denny Sagita Rusdianto; Eriq Muhammad Adams Jonemaro (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
CV Sitiari is a domestic worker supplier foundation that distributes maids, babysitters, and also carers for the elderly. In doing business, there were several problems that were felt by CV. Sitiari. The first problem is the difficulty of synchronizing data for domestic workers and employers from one branch to another, all transaction data, employees and customers are synchronized between branches using Microsoft Excel, WhatsApp, and SMS. This makes inter-branch synchronization ineffective. The second problem is recording errors in orders and payments. Recording of orders and payments that are still done manually causes synchronization between employees who handle orders and employees who handle payments to be ineffective and errors often occur. Based on these problems, a management system development and ordering services for domestic workers were carried out that could solve the problems on CV. Sitiari. The software development process in this study was carried out using the Waterfall method. The stages carried out in this research are literature study, requirement analysis, system design, implementation, testing, and drawing conclusions and suggestions. This system was developed based on web and PHP programming language. This system uses Midtrans as a payment gateway. Unit testing was carried out by the white-box testing method and produced 100% valid data from 3 test cases. Validation testing used the black-box testing method and produced 100% valid data from 39 test cases. The compatibility test was carried out with 100% valid results.